The effect of TRX exercises on developing health-related fitness among participants in fitness centers - Omar, L.Dr.Karwan Ali; Rafiq, Prof.Dr.Heval Khurshid (Sulaimani Journal for Humanities, 2026)
Through their observations as specialists in training and fitness, and their frequent visits to fitness centers, the researchers found that many trainers do not favor diversifying exercises to develop physical fitness, relying primarily on weight training without other training methods. The underlying problem that motivated the researchers to conduct this study is the lack of use of other methods to develop health-related fitness instead of weight training. The research aims to develop TRX exercises for participants in fitness centers and to identify the effect of TRX exercises on developing health-related fitness among these participants. The researchers hypothesize that TRX exercises are superior to traditional training methods. The researchers used a single-group experimental design, deemed suitable for the nature of the research. The sample consisted of ten participants from the Aka Fitness gym in Erbil. The researchers statistically analyzed the results using the SPSS statistical package. The researchers concluded that TRX exercises have a significant advantage in developing health-related fitness among the research sample and that regular TRX exercises can help maintain and improve health, fitness, and quality of life.